MODEL PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH (UMKM) DALAM REVITALISASI KAMPUNG TEKSTIL - L. Gaol, Denada; Rinny, Meidiyustiani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2018)
This study aims to illustrate the model of Small Medium Enterprises (SMEs) empowerment in the revitalization of textile village in Cipadu Market. The market’s neighbourhood could be categorized as slum area and there are lacks of facilities and supporting infrastructure. This research uses quantitative approach, analysis descriptive of method, primary and secondary data, data collection technique through observation, interview, questionnaire, and literature study. Data analysis technique includes data collection, data reduction, data analysis, and make conclusions. The results of this study indicates that to make the model of empowerment of SMEs involves several related parties such as financial institution as fund provider, Board of Cooperatives and SMEs Tangerang City as regulator, local credit guarantee company (Jamkrida Banten) as guarantor of business capital loan of SMEs, the company is in charge of increasing knowledge and educating the SMEs to be more professional in running the business, and not less important, SMEs itself as the key in empowerment process should improve their own quality and skills in running the business until the target of revitalizing the textile village in the cluster industry and infrastructure improvements is achieved.